2017
DOI: 10.1186/s12870-017-1117-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of Sharka disease tolerance in peach (P. persica L. Batsch)

Abstract: Background Plum pox virus (PPV), agent of Sharka disease, is the most important quarantine pathogen of peach (P. persica L. Batsch). Extensive evaluation of peach germplasm has highlighted the lack of resistant sources, while suggesting the presence of a quantitative disease resistance, expressed as reduction in the intensity of symptoms. Unravelling the genetic architecture of peach response to PPV infection is essential for pyramiding resistant genes and for developing more tolerant varieties. For this purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Tolerance to tomato yellow leaf curl virus is also associated with single dominant genes in wild tomato species and was successfully introgressed into cultivated tomato ( Zamir et al, 1994 ; Vidavsky and Czosnek, 1998 ). In peach, tolerance to plum pox virus (a potyvirus) was mapped to three loci ( Cirilli et al, 2017 ). One of these loci included a candidate gene with similarities to the A. thaliana RTM-2 gene, which is implicated in the restriction of the systemic movement of other potyviruses ( Cirilli et al, 2017 ).…”
Section: Insights In the Complexity Of Tolerant Plant–virus Interactimentioning
confidence: 99%
See 1 more Smart Citation
“…Tolerance to tomato yellow leaf curl virus is also associated with single dominant genes in wild tomato species and was successfully introgressed into cultivated tomato ( Zamir et al, 1994 ; Vidavsky and Czosnek, 1998 ). In peach, tolerance to plum pox virus (a potyvirus) was mapped to three loci ( Cirilli et al, 2017 ). One of these loci included a candidate gene with similarities to the A. thaliana RTM-2 gene, which is implicated in the restriction of the systemic movement of other potyviruses ( Cirilli et al, 2017 ).…”
Section: Insights In the Complexity Of Tolerant Plant–virus Interactimentioning
confidence: 99%
“…In peach, tolerance to plum pox virus (a potyvirus) was mapped to three loci ( Cirilli et al, 2017 ). One of these loci included a candidate gene with similarities to the A. thaliana RTM-2 gene, which is implicated in the restriction of the systemic movement of other potyviruses ( Cirilli et al, 2017 ). However, functional validation will be required to confirm whether the RTM-2 -like gene is indeed responsible for the tolerance.…”
Section: Insights In the Complexity Of Tolerant Plant–virus Interactimentioning
confidence: 99%
“…An extensive evaluation of a peach gene pool collection (germplasm) showed that PPV resistance is probably quantitatively based and is manifested as a decrease in symptom intensity (Cirilli et al, 2017). For this reason, it is important to disclose the genetic architecture of the response of peach trees and their relative species to PPV infection, which is necessary for pyramiding of resistant genes and for development of more tolerant species and rootstocks.…”
Section: Rootstockmentioning
confidence: 99%
“…The sequencing of 'PI91459' ('NJ Weeping') and 'Bounty' parents was performed at the Genomics Platform of Parco Tecnologico Padano (Lodi, Italy) following the protocol described by Cirilli et al (2017). Functional annotation of the variants was performed using SNPEFFECT 2.0 (Reumers et al, 2006).…”
Section: Whole-genome Sequencingmentioning
confidence: 99%